Penerapan Fintech E-Wallet Dana Sebagai Alat Transaksi Dalam Menunjang Sistem Informasi Akuntansi Penjualan Pada UMKM Dimsum Bestie - Supyan, Ita Suryanita; Sidik, Alief Moch (JEMSI (Jurnal Ekonomi, Manajemen, dan Akuntansi), 2025)
As digital technology continues to develop, micro, small, and medium enterprises (MSMEs) have begun to utilize financial technology to support their sales accounting information systems. One innovation being adopted is the use of digital wallets or E-Wallets such as DANA. This study aims to determine whether the DANA E-Wallet Fintech has been used in transaction processes at the MSME Dimsum Bestie and how it is implemented to support its sales accounting information system. Furthermore, the study seeks to identify the benefits and challenges faced by Dimsum Bestie in using the DANA E-Wallet Fintech. This research employs a qualitative method with a case study approach. Data collection techniques include interviews, direct observation, and document study. The results indicate that Dimsum Bestie has implemented the DANA E-Wallet as a payment transaction method due to its practicality and security. The use of this e-wallet facilitates automatic transaction recording, enhances efficiency, and simplifies financial reporting. However, there are challenges such as the minimum withdrawal limit of IDR 50,000, which is considered less flexible. Additionally, the accounting information system is still managed solely by the owner, without a clear separation of functions. In conclusion, the DANA E-Wallet has made a positive contribution to the effectiveness of sales recording and financial transparency, although improvements are still needed in internal control aspects.